A separação de poderes e a efetividade do Estado Democrático de Direito - Fernandes, Patricia Stefoni (2019)
The purpose of this study is to explore the Theory of Separation of Powers and to understand the extent to which it is possible for a Democratic Right State to exist and be maintained without it being truly effective. The separation of powers was conceived and developed to contain the abusive and distorted manifestation of power by political agents, but it is not limited to the existence of the Legislative, Executive and Judiciary branches. It goes far beyond that. Each of the state functions has received special attention from various Constitutional Letters in terms of limits and competencies, and all of them, together, need to serve a greater purpose. All the concepts that are linked to the Theory, all the institutes that intertwine with it were analyzed in this work, in order to seek to understand clearly if there is effectiveness of the Theory of Separation of Powers today and to what extent this effectiveness (or its absence) reverberates in the fullness of the democratic rule of law